DAMPAK VIDEO GAME TERHADAP PERKEMBANGAN PERILAKU ANAK UMUR 3-6 TAHUN DI DESA BANARAN KECAMATAN PRACIMANTORO KABUPATEN WONOGIRI - Nurnawati Hindra H, Lilik Rahmawan Randi Santoso, Maya Sekar Wangi & (Transformasi, 2018)
Video game is one of the game can’t be separated from the children, because its their time to play. A video game is an electronic game that involves interaction with a user interface to generate visual feedback on a video device. Video game has a positive and negative effect especially for children within age 3 - 6 years old in Banaran Village, Pracimantoro, Wonogiri which has been facilitated with smartphone although it just for playing a video game.Outline of the problem is how the effect of video game against the growth of children aged 3 - 6 years old in Banaran Village, Pracimantoro, Wonogiri.The purpose of reseach to describe and analyze how the effect of video game against the growth of children behavior aged 3 - 6 years old in Banaran Village, Pracimantoro, Wonogiri.This research based on theoryst icluding positive and negative effect, describtion of video game, and the growth of children behavior theory.Type of reseach is qualitative descriptive ; Location of research in Banaran Village, Pracimantoro, Wonogiri ; 9 informants were used for Naturas setting technique in this research.. Type of data using primary data and secondary data. The ways observation, interview, and documentation. Data analysis technique done interactively and continually until the last consist of reduction data, served data, and conclusionResult of the research indicate that the video game has positive and negative effect, the positive effect of video game is just lighten the burden of parent at the time thew want to do the housework and can sharper the memory. The negative effect for children they can dispute their parent, dare to fight with their parent, have no manners, can’t be given an advice, being anti social, communication with parent is not going well. It can be concluded that the effect of video game against the growth of children aged 3 - 6 years old in Banaran Village, Pracimantoro, Wonogiri have more negative effect than positive effect.Keywords : video game, effect, the growth of the children behavior